Extraction and Characterization of Fish Collagen for Enhanced Wound Healing Activity on A549 Cell Lines - Anbuselvan, Vimal Arasan; Nelson, Bliss Shiny; Karunaharan, Bhavya; Kandhasamy, Sivakumar (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2024)
Collagen is a proteinaceous material that is present abundantly in animal tissues and gives physical strength and stability to the tissues. Collagen extracted from animal tissues has been applied in the biomedical and healthcare sectors. In recent days, aquatic organisms have shown great potential for collagen extraction and purification. In the present study, we selected three fish species: Naucrates ductor, Oreochromis mossambicus and Cyprinus carpiofor collagen extraction from both their skin and scales. The biomass was pre-treated to remove any non-collagenous matter and fat. Acid-soluble collagen was extracted using acetic acid and a maximum extraction of 51.55±1.02% was reported. The total protein fractions and the denaturation temperatures of the collagen extractswere measured. The molecular weights and the subunit compositions of the collagen extracts were analyzed using SDS-PAGE and the presence of two α chains, one β, and one γ chain. Amino acid profiling was done in an amino acid analyzer after hydrolysis and about one third of the total amino acid content was glycine. The solubility characteristics of the collagenextracts were analyzed at different ranges of pH and salinity. The antimicrobial activities of the collagen extracts were examined against four bacterial species, and it was proven that skin-derived collagens had greater antibacterial potential than extracts of the scales. In vitro studies on the wound healing capacity of the extracted collagen were performed using A549 cell line cultured in F-12K medium, and 95% of cell regeneration was observed in collagen-supplemented dispersed cell lines.